Combined Orthokeratology with Atropine for Children with Myopia: A Meta-Analysis - Wang, Suzhen; Wang, Jie; Wang, Ningli (Ophthalmic research, 2021)
Background: Myopia has become a worldwide public health issue, which is occurring at a younger age, leading to an increased risk of high myopia. Ocular complications associated with high myopia can lead to irreversible vision loss. It is urgent and critical to explore effective treatment to slow down or even stop the progression of myopia in young children. Objective: The aim of the study was to evaluate the additive effects of orthokeratology (OK) and 0.01% atropine ophthalmic solution for myopia in children. Methods: We searched PubMed, Cochrane Library, EMBASE, MEDLINE, Web of science, Ovid, EBSCO host, CNKI, and CBM to collect eligible studies. Efficacy and safety were evaluated in terms of the axial length (AL), uncorrected distant visual acuity (UCVA), corneal endothelial cell density (CECD), and intraocular pressure (IOP). We calculated the weighted mean difference (WMD) and the 95% confidence intervals (CIs) of all outcomes and plotted on forest plots. Results: Four studies were ultimately included, involving a total of 267 subjects. This meta-analysis revealed that the mean AL of the subjects in the experimental group was 0.09 mm less than that of subjects in the control group (WMD = −0.09, 95% CI [−0.15, −0.03], p = 0.003). There was no significant difference in UCVA, CECD, and IOP between the 2 groups (WMD was −0.01 [95% CI: −0.03, 0.01], 11.75 [95% CI: −4.09, 27.58], 0.12 [95% CI: −0.40, 0.63], respectively). None of the studies reported severe adverse events. Conclusion: Our study suggests that the combination of OK and 0.01% atropine is more effective in slowing axial elongation than OK monotherapy in children with myopia in a relatively short duration of treatment. In addition, the combination therapy has no negative influence on UCVA, CECD, and IOP.